2020
DOI: 10.1159/000509823
|View full text |Cite
|
Sign up to set email alerts
|

Imaginal Retraining Reduces Cigarette Smoking: A Randomized Controlled Study

Abstract: Objectives: Smoking is a highly prevalent addictive behavior with severe and life-shortening health consequences. This is the first study to evaluate the efficacy of a newly developed imaginal variant of approach bias modification (ABM) (i.e., imaginal retraining) for the reduction of craving for tobacco and actual smoking behavior. Methods: We randomized 345 smokers to imaginal retraining (self-help manual) or a control group (either active control or wait-list control). Assessments were carried out online. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…Results suggest that some prior practice of the technique may indeed foster effectiveness. In the current (full) protocol of imaginal retraining, we suggest that participants use smartphone timers to remind them to perform the technique as there is increasing support that frequent practice augments the outcome 21 , 23 . Future studies may also adopt a more balanced factorial design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results suggest that some prior practice of the technique may indeed foster effectiveness. In the current (full) protocol of imaginal retraining, we suggest that participants use smartphone timers to remind them to perform the technique as there is increasing support that frequent practice augments the outcome 21 , 23 . Future studies may also adopt a more balanced factorial design.…”
Section: Discussionmentioning
confidence: 99%
“…A formal diagnosis of tobacco dependence or fulfillment of any threshold criteria was not mandatory. For further details on recruitment, mode of assessment, and the initial technique, see the original study 21 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaginal retraining is a non-computerized technique taking the limitations mentioned before into account, merging imaginal and behavioural components. Previous studies have demonstrated the efficacy of imaginal retraining across a variety of addictive behaviours, such as excessive high-calorie food consumption [ 21 ], problem drinking [ 27 ] and cigarette smoking [ 28 ]. Imaginal retraining transfers the classical AAT into one’s own imagination.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a benefit of dismantling effective mechanisms would be to design simpler and briefer interventions. Moreover, previous imaginal retraining interventions were usually implemented for the duration of 1 month [ 21 , 27 , 28 ]. A question of interest is therefore whether a single implementation of the imaginal retraining technique could already have a significant and relevant effect on reducing craving and appraisal for high-calorie food.…”
Section: Introductionmentioning
confidence: 99%